Un’applicazione di indicatori, basata sulla ricerca, per misurare la qualità dell’istruzione - Jaap Scheerens; Jan van Ravens; Hans Luyten (Journal of Educational, Cultural and Psychological Studies, 2011)
A Research Based Application of Indicators to Measure Educational Quality